PG91 Simulating to bridge the gaps: using high fidelity simulation to expose ACCS trainees to uncommon but vital skills. (10th November 2020) - Chanin, Tobias; Wise, Daniel; Walsh, Ciaran; Wharton, Tim; Parr, Tim; Mercer, Simon
Abstract : Background: The acute common care stem (ACCS) training programme exposes junior doctors to a wide array of acute medical specialities and includes spending 6-months in each of acute medicine, emergency medicine, anaesthetics and intensive care. The trainees undertaking this programme will end up being consultants in acute specialities, regularly facing deteriorating patients, who require time-critical interventions. It is vitally important that these skills are obtained during their training. Previous years of ACCS trainees have highlighted the difficulty in completing some key skills due to lack of time, exposure and opportunity. We report a one-day fully immersive simulation course designed and piloted in our institution, aiming to expose trainees to these vital skills. Summary of Work: The course used a programme of spiral learning, with technical skill sessions in the morning, giving the candidates a grounding in the skills and their indications. The afternoon consisted of 4 high-fidelity simulated-patient scenarios that exposed candidates to the practical aspects of the procedures, and crucially, the opportunity to exercise their decision-making skills. The key procedures included intraosseous needle insertion, transcutaneous pacing, electrical cardioversion and surgical chest drain insertion. To simulate intraosseous needle insertion, our team devised a close-to-life model that could be inserted into the arm of a wireless mannequin. This allowed candidates to perform the skill without the need to 'break away' and use another model, thus increasing immersion in the scenario. We asked candidates to complete pre and post-course questionnaires to measure change in self-assessed confidence (Likert 0–10) [1] related to performing these skills. Summary of Results: Twenty-one candidates have completed the course, to date with participation in a minimum of 2 scenarios each. An unpaired (two tail) t-test analysis of results indicated statistically significant increases in confidence scores regarding performing intraosseous needle insertion (3.7 to 8.42/10 improvement) and cardioversion/transcutaneous pacing (5.3 to 8.6/10 improvement). Course usefulness was rated 9.6/10, with candidates scoring scenarios and workshops at least 9.52/10 in satisfaction. Discussion and Conclusions: We have demonstrated that high fidelity simulation, used in combination with more traditional teaching, can vastly improve perceived confidence of trainees with regards to skill acquisition. Courses of this format give trainees the opportunity to map core skills to their curriculum and complete workplace-based assessments, closing an educational gap that has the potential to put patients at risk. This means no trainee would be left behind and unable to progress due to a lack of opportunity or exposure. Reference: Likert R. A technique for the measurement of attitudes. Archives of Psychology 1932; 140: 1–55.